Dream types a domain specific type system for component-based message-oriented middleware. - Bidinger, Philippe (Software engineering notes.)
We present a type system for the Dream component-based message-oriented middleware. This type system aims at preventing the erroneous use of messages, such as the access of missing content. To this end, we adapt to our setting a type system developed for extensible records.